3D Electroanatomic Mapping of an Extreme Oblique Accessory Pathway in Wolff-Parkinson-White SyndromeNovel Teaching Points - David Nelson, BSc; Clarence Khoo, MD, FRCPC (CJC Open, 2020)
A high-risk left-sided posterolateral manifest accessory pathway (AP) was identified in a 49-year-old man. Two prior ablations had failed. A repeat procedure using 3D electroanatomic mapping demonstrated an extremely oblique AP. The earliest atrial activation site was not amenable to endocardial ablation. The earliest ventricular activation site was identified, demonstrating an AP with an extremely slanted course. Radiofrequency ablation here resulted in sustained bidirectional AP block. In challenging AP ablation cases, recognition of the potential for an oblique AP and the use of electroanatomic mapping may be beneficial. Résumé: Une voie accessoire (VA) apparente postéro-latérale gauche à haut risque a été identifiée chez un homme de 49 ans. Deux ablations antérieures avaient échoué. Une procédure répétée utilisant la cartographie électroanatomique 3D a révélé une VA extrêmement oblique. Le site ayant l’activation auriculaire la plus précoce ne se prêtait pas à une ablation endocardique. Le site ayant l’activation ventriculaire la plus précoce a été identifié, montrant une VA avec une trajectoire extrêmement inclinée. L'ablation par radiofréquence a ici entraîné un bloc bidirectionnel soutenu de la VA. Dans les cas difficiles d'ablation de VA, la reconnaissance du potentiel d'une VA oblique et l'utilisation de la cartographie électroanatomique peuvent être bénéfiques.